2002
DOI: 10.1354/vp.39-1-92
|View full text |Cite
|
Sign up to set email alerts
|

Canine T-cell Lymphomas: A Morphological, Immunological, and Clinical Study of 46 New Cases

Abstract: The aim of this study is to report 46 new cases of canine T-cell lymphomas among a series of 140 lymphomas studied by immunophenotyping (incidence 32.8%). According to the updated Kiel classification adapted to the canine species, 13 were classified as low-grade and 33 as high-grade lymphomas. Among the low-grade lymphomas, five were small clear-cell lymphomas, three were pleomorphic small-cell lymphomas, and five mycosis fungoides. Among the high-grade cases, there were 11 pleomorphic mixed-, small-, and larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
205
5
24

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(260 citation statements)
references
References 71 publications
26
205
5
24
Order By: Relevance
“…The CD3 is a speciϐic marker for T lymphocytes (Fournel-Fleury et al 2002). In this study, 92% (34/37) of the CLs were positive for CD3.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The CD3 is a speciϐic marker for T lymphocytes (Fournel-Fleury et al 2002). In this study, 92% (34/37) of the CLs were positive for CD3.…”
Section: Discussionsupporting
confidence: 53%
“…Similar to what occurs in humans, the determination of the immunophenotype of lymphoma in dogs has become essential because of the relationship to biological behavior and response to therapy (Fontaine et al 2010, Fournel-Fleury et al 2002. Currently, the immunohistochemical markers most commonly used to characterize T and B lymphocytes in formalin--ϐixed, parafϐin-embedded tissues include CD3 (Fournel--Fleury et al 2002) and CD79a (Milner et al 1996), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…T‐cell lymphoma (TCL) accounts for approximately 10‐38% of canine non‐Hodgkin's lymphoma (LSA) 1, 2. The disease is considered to have a more aggressive clinical course and is associated with a poorer prognosis (6–9 months median survival) when compared to B‐cell lymphoma (BCL; 12–14 months median survival) 3…”
mentioning
confidence: 99%
“…In veterinary clinical science, some studies indicate that the updated Kiel classification is applicable to canine lymphomas [6,7,17,19,22]. One of the studies reported that the first remission duration and the overall survival time were significantly different among the subtypes of lymphomas [17].…”
mentioning
confidence: 99%